Antibiofilm action of Persea americana glycolic extract over Acinetobacter baumannii and absence of toxicity in Galleria mellonella - Dos Santos Liberato, Sabrina Ferreira [UNESP]; Da Cruz Vegian, Mariana Raquel [UNESP]; Abu Hasna, Amjad [UNESP]; De Alvarenga, Janaína Araújo [UNESP]; Dos Santos, Juliana Guimarães [UNESP]; Tini, Ítalo Rigotti Pereira [UNESP]; Amêndola, Isabela [UNESP]; Junqueira, Juliana Campos [UNESP]; De Oliveira, Luciane Dias [UNESP] (De Gruyter, 2021)
This study aimed to evaluate the antibiofilm activity and toxicity of the glycolic extract of Persea americana P. americanaover multidrug-resistant strains of Acinetobacter baumannii A. baumanniias alternative therapy to be investigated. A bacterial inoculum of each bacterial strain (4a, 5a, 9a, 12a, ATCC 19606) of A. baumannii was prepared and adjusted by the spectrophotometer. The microdilution broth method was performed to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). P. americana glycolic extracts were obtained of the tree stalk and leaves. The biofilm viability was tested by MTT assay after 5 min exposure. The toxicity of the extracts was tested by invertebrate model Galleria mellonella. The data were analyzed by ANOVA, Tukey test and log-rank method (α=0.05). The extract showed an inhibitory and bactericidal action over all the tested strains with the lowest MIC value observed for the reference strain (3.12 mg/mL). The extract did not demonstrate toxicity in any of the tested concentrations (12.5, 25 and 50 mg/mL) in Galleria mellonella larvae, with a survival percentage above 80% after 168 h. The glycolic extract of P. americana has microbicidal and antibiofilm activity on multidrug-resistant clinical strains of A. baumannii and showed low toxicity for the invertebrate model G. mellonella.
Keywords: Acinetobacter baumannii; antibacterial agents; Persea americana; phytotherapy